2016
DOI: 10.2527/jas.2016-0648
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of phase feeding and valine-to-lysine ratio during lactation on sow and piglet performance1

Abstract: The potential of piglets to grow before weaning is greater than the sow can support, and as such, improving the performance of the lactating sow is a key driver of whole-farm efficiency. This study aimed to investigate the impact of 1) adopting a phased feeding approach during lactation and 2) the ratio of Val to Lys on sow and piglet performance. Multiparious sows ( = 109) were assigned to treatment at 108 d of gestation. Dietary treatments were arranged in a 2 × 2 + 1 factorial design. Dietary treatments inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
4
7
0
1
Order By: Relevance
“…Therefore, the effect of maternal diet on milk production increases as lactation progresses [40]. Previous research on increasing sow milk yield by increasing dietary energy density was not successful [41]. Similarly, in the present study, increasing sow energy intake in late lactation did not increase sow milk yield as measured indirectly from piglet growth, with sow milk yield appearing to plateau on day 14, which is in agreement with previous research [41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the effect of maternal diet on milk production increases as lactation progresses [40]. Previous research on increasing sow milk yield by increasing dietary energy density was not successful [41]. Similarly, in the present study, increasing sow energy intake in late lactation did not increase sow milk yield as measured indirectly from piglet growth, with sow milk yield appearing to plateau on day 14, which is in agreement with previous research [41].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research on increasing sow milk yield by increasing dietary energy density was not successful [41]. Similarly, in the present study, increasing sow energy intake in late lactation did not increase sow milk yield as measured indirectly from piglet growth, with sow milk yield appearing to plateau on day 14, which is in agreement with previous research [41]. In the present study, the fatty acid composition of milk at day 21 of lactation, as well as of piglet plasma and tissues at weaning were affected by dietary energy density.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, sows had a mean litter gain of 3.25 kg/d, emphasizing that the lactation performance is really high in modern hyper prolific sows. In line with that, Thingnes et al (2012) and Craig et al (2016) reported a daily litter gain of 3.12 and 3.24 kg/d, respectively. For comparison, daily litter gain is normally considerably lower in sows with less suckling piglets (10 to 12 littermates), and the productivity of these sows are typically 2.3 kg/d to 2.7 kg/d (e.g., Huber et al, 2015 andGreiner et al, 2018).…”
Section: Sow Mobilizationsupporting
confidence: 86%
“…However, the previous recommendations were based on few studies. In agreement with the current study, previous literature have proven that SID Val:Lys-ratios at 65%-70% does not compromise sow productivity (Paulicks et al, 2003;Craig et al, 2016;Højgaard et al, 2019).…”
supporting
confidence: 94%